Bacillus subtilis from Potato Rhizosphere as Biological Control Agent and Chili Growth Promoter - Nur Prihatiningsih; Heru Adi Djatmiko; Erminawati Erminawati; Puji Lestari (Jurnal Perlindungan Tanaman Indonesia, 2019)
Bacillus subtilis is an antagonist bacteria  that inhibits the growth of fungal and bacterial plant pathogens. The B. subtilis has roles as biocontrol agents and plant growth promoting rhizobacteria (PGPR). This research aimed to evaluate the potency of B. subtilis isolates (B209, B211, and B298) as a biocontrol agent to anthracnose (caused by Colletotrichum spp.) and as PGPR to increase the growth of chili plants. The experiments were divided into two batches. The first batch was conducted in the laboratory to evaluate the characteristics of B. subtilis (as biocontrol) and PGPR (phosphate solubility, producing IAA and nitrogen). The second batch was conducted in the field in Rempoah Village, Baturraden Regency, Banyumas District, with 5 treatments and 6 replications. Parameters observed were inhibition percentage to Colletotrichum spp., disease intensity, the component of PGPR, plant growth of chili, and phatosystem. The results showed that B209, B211, and B298 isolates inhibited the growth of Colletotrichum spp, with the highest inhibition percentage on B298. B209, B211, and B298 have characteristics as PGPR, i.e. the ability to soluble phosphate, to produce IAA and nitrogen. The ability of B298 to promote plant growth was shown by the increase of plant height, leaf number, plant dry mass, and dry root mass (38.0%, 54.7%, 61.7%, 61.8%, respectively). B298 and B211 could increase the fresh crop mass (41.2% and 37.1%) and fresh root mass (36.4% and 34.4%). B298 and B209 were similar in increasing the root length (25.2%). Root volume could be increased by 33.3% by applying B211 isolate. B209 was the best isolate to reduce anthracnose up to 80.36%.